An Examination on the Impact of Reading Strategies Employed by Secondary School Students on Their Reading Performance and the Role of Gender on the Use of These Strategies - Berhe, Elfinesh; G/Mariam, Alamirew (Loquen, 2025)
This study aimed to investigate the relationship between students’ strategy use and their reading performance, particularly highlighting any notable differences between male and female students. To this end, one hundred and thirty (71 female and 59 male) grade nine students participated in the study. Data was collected using the TOEFL reading comprehension test and the Metacognitive Reading Strategy Inventory (MARSI). The Statistical Package for the Social Sciences (SPSS) version 24 was utilized for data analysis. Descriptive statistics, including frequencies, means, and standard deviations, were utilized to determine the extent of students’ awareness and utilization of reading strategies. Moreover, the Pearson correlation coefficient was employed to examine the association between strategy usage and reading performance. An independent sample t-test was also conducted to identify any differences in strategy usage between male and female students. The result showed a significant relationship between the utilization of strategies and reading performance. The t-test indicated no notable differences in overall strategy usage between male and female students collectively. When examining the achievement levels of male and female students, significant differences in strategy usage was found for both low and high achievers. However, there were no significant differences identified among male and female students performing at a medium level. The study suggests that ninth-grade students would benefit from enhanced opportunities to employ effective reading strategies. Future research could build on these findings by expanding the scope of the investigation.